2011
DOI: 10.3109/00365513.2011.599416
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in predicting short- and long-term morbidity and mortality in patients with or without ST-segment elevation myocardial infarction

Abstract: Mean platelet volume (MPV) is a marker of platelet activation. An increased MPV is associated with acute myocardial infarction (AMI) and long-term mortality. The aim of this study was to compare MPV in patients with ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI). Also, we investigated the value of MPV on in-hospital mortality and long-term prognosis of patients with STEMI and NSTEMI. We studied 429 patients with AMI (70.4% male, 61.9 ± 12.4 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
0
29
1
1
Order By: Relevance
“…In some studies conducted in AMI, elevated MPV was associated with higher risk of death and recurrent infarction not only in hospital but also during the 2 years observation after ACS [2,[19][20][21][22]. Taglieri et al [7] investigated higher risk of primary end-point, composed of cardiovascular death and re-MI at 1 year after ACS in patients with NSTEMI with MPV ³ 8.9 fl.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies conducted in AMI, elevated MPV was associated with higher risk of death and recurrent infarction not only in hospital but also during the 2 years observation after ACS [2,[19][20][21][22]. Taglieri et al [7] investigated higher risk of primary end-point, composed of cardiovascular death and re-MI at 1 year after ACS in patients with NSTEMI with MPV ³ 8.9 fl.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recognized as an independent risk factor for MI, but not for coronary artery disease prevalence [6,7]. Measured at 6 months after acute MI, MPV has been shown to predict recurrent MI and death in 2-year follow up [8]. In ST-segment elevation MI treated with percutaneous coronary intervention (PCI), MPV has been observed to be a strong, independent factor of impaired angiographic reperfusion and 6-month mortality [9].…”
Section: Introductionmentioning
confidence: 99%
“…15 In the scenario of myocardial infarction, it has been shown that the MPV measured six months after the event was able to predict recurrent infarction and mortality in 2 years. 16 In 2005, Huczek et al 17 demonstrated in 398 patients undergoing PPCI that MPV measured before the procedure was a strong independent predictor of reperfusion failure and mortality in 6 months. No-reflow phenomenon was observed in 21.2% vs. 5.5% (p = 0.0001), when comparing patients with MPV greater to or equal and lower than 10.3 fL, respectively.…”
Section: Discussionmentioning
confidence: 99%